Realization and dosimetric characterization of a mini-beam/flash electron beam - Pensavalle, Jake Harold; Romano, Francesco; Celentano, Mariagrazia; Sarto, Damiano Del; Felici, Giuseppe; Franciosini, Gaia; Masturzo, Luigi; Milluzzo, Giuliana; Patera, Vincenzo; Prezado, Yolanda; Di Martino, Fabio (Frontiers in Physics, 2023)
The use of the flash effect and mini-beams have demonstrated the ability to spare healthy tissue while maintaining the same effectiveness in controlling tumors. In this study, we present the implementation and comprehensive dosimetric characterization of low-energy mini-beam radiation therapy at both conventional and ultra-high dose rates. These beams possess important features that allow for a wide range of spatial and temporal parameter variations, independently or simultaneously, for both effects. This novel capability enables the performance of in vivo/vitro radiobiological experiments, which are crucial for understanding the underlying mechanisms and quantitative dependencies of these effects on their respective parameters. This understanding is essential for evaluating the potential clinical applications of the two effects both individually and in terms of their potential synergistic actions.